The Fleet and Berth Selection Model to Improve Energy and Environment Sustainability - Ari Setiawan; Eka Kurnia Asih Pakpahan; Hadi Susanto (School of Industrial and System Engineering, Telkom University, 2023)
This research aims to improve energy sustainability in transportation management. The case wasderived from port-to-port coal transportation problem commonly faced by third-party logistic (3PL)company. During planning, they must determine which shipsets to be used and assign them to theloading/unloading berths. Each berth varies in terms of its loading/unloading speed and each shipsetvaries in terms of its capacity, sail speed, and fuel consumption rate. The selection of shipset impactsthe auxiliary and main engine fuel consumption while the selection of berth impacts only the auxiliaryengine fuel consumption. The target is to minimize the total fuel consumed by both engines for thewhole shipset. We modelled the case through Multiple Vehicle Allocation Problem (MVAP)framework and proposed a heuristic algorithm to find the solutions. The heuristic algorithm is provento be able to reach an optimal solution for small cases and near-optimal for medium to large cases.